Reação de acessos e herança da resistência Macrophomina phaseolina e efeito da temperatura na podridão cinzenta em meloeiro - Linhares, Cheyla Magdala de Sousa (2018)
Although the melon has an excellent adaptation to the predominant edaphoclimatic conditions in the Brazilian Northeast region, some factors have contributed to the decrease in productivity and fruit quality, such as the occurrence of diseases caused by soil microorganisms, especially gray rot stem, occasioned by Macrophomina phaseolina Tassi (Goid.). The objectives of the present work were: to evaluate the access reaction, the inheritance of the resistance to M. phaseolina, and the effect of the temperature on the gray rot in melon. For the study of the reaction were evaluated 46 accessions in a greenhouse, in a completely randomized design with five replicates. The experimental unit consisted of a vessel with a plant. Sowing of the accesses was carried out directly in the vessels, containing sterilized commercial substrates. The inoculation of M. phaseolina was carried out by means of the direct insertion of the toothpick infested with structures of the fungus near the plant 's neck at 20 days after sowing. Fifteen days after inoculation of the fungus, the severity of the disease was evaluated using a scale of grades. In the second experiment, the inheritance of Ag-15591Ghana (resistant) cross-resistance was investigated with In-PsPiñSp (susceptible). In order to evaluate the effect of the temperature, the accessions Ag-15591Ghana, Con-Pat81Ko, Ag-C38Nig, In-PsPiñSp, Can-NYIsr and Dud-QMPAfg were inoculated by the stick method with the Me-248 isolate and maintained at different temperatures 25, 28, 31 and 34 ° C) for ten days. Variability was observed in the germplasm investigated for fungal reaction. Ag-15591Ghana access is resistant to M. phaseolina and its resistance is controlled by a major gene of additive and dominant effect and polygenes of additive effects. The elevation of temperature increases the severity of the gray rot caused by M.phaseolina in melon. In-PsPiñSp access is more susceptible at temperatures 28, 31 and 34 ° C. The Com-Pat81Ko, Ag-C38Nig, Can-NYIsr and Dud-QMPAfg accessions are resistant at temperatures 25, 28 and 31 ° C, but susceptible at 34 ° C. Ag-15591Ghana access is a promising source for breeding programs of melon because its resistance to M.phaseolina is slightly altered by the increase in temperature